2019
DOI: 10.1111/nuf.12420
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study of influences on long‐term physical activity in physically active African American women

Abstract: Performing routine physical activity (PA) is one of several measures that may be taken to prevent chronic illness; however, African American (AA) women are among the least physically active groups in the United States. The purpose of this study was to gain perspectives of AA women who are physically active and understand how they continue long-term PA. In this qualitative descriptive study, we interviewed 14 AA women using researcher-developed open-ended questions. Transcription was analyzed through content an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…Some women discussed including their family in their physical activity to help with accountability. “It, it helps me because, like I said, a lot of times when I get off work… I don’t feel like doing anything… so what they [family] have done for me recently is … [they] still hold me accountable; ‘let’s go walk outside’ or… if we’re going to the mall, ‘let’s just take two laps,’ even though we’re going to the mall for something else .” 37 Others utilize their family and want to remain involved as a motivator for physical activity. “For me, I think it comes to normalcy, I guess.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some women discussed including their family in their physical activity to help with accountability. “It, it helps me because, like I said, a lot of times when I get off work… I don’t feel like doing anything… so what they [family] have done for me recently is … [they] still hold me accountable; ‘let’s go walk outside’ or… if we’re going to the mall, ‘let’s just take two laps,’ even though we’re going to the mall for something else .” 37 Others utilize their family and want to remain involved as a motivator for physical activity. “For me, I think it comes to normalcy, I guess.…”
Section: Resultsmentioning
confidence: 99%
“…I want to be able to take care of myself for a long time (laughs)." 37 Other participants emphasize the importance of physical activity to live a long healthy life. "For me, the motivating factor is I want to live.…”
Section: "[Be]cause We All Do Very Different Kinds Of Physical Activi...mentioning
confidence: 99%
“…These findings are similar to other studies that have reported a range of social support from friends. 8,12,13,22,30 Sallis et al, (1987) reported that support for exercise from friends in the form of 'exercising together' was important among active individuals as well as those desiring to become more active. 12 Furthermore, Johnson et al, (2014) also found that rural Black women participating in weight loss trial reported that friends provided support by joining in exercise with participants even if it required altering their schedule.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, Hubbell et al, (2020) reported only positive support from friends suggesting a shift in social norms for PA among Black women. 30 Across categories of PA engagement, it appeared that 'people' was the most important factor for Black women engaging in PA long-term. The roles of 'people' ranged from a PA partner to those providing instruction and were similar to the four companionship roles that emerged from focus groups with active Black women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation